Variáveis limnológicas e estruturais do habitat predizem a diversidade funcional e a composição das comunidades de peixes em lagoas de planície de inundação. - Rodrigues, Amanda Cantarute (2018)
It was investigated in which way the environmental variation created on floodplain lagoons explains the variation of fish assemblages. It was evaluated one taxonomic index and two functional indices of fish communities from six floodplain lakes of the upper Paraná River floodplain, investigating if their changes depend of the same set of predictors. It was predict that the taxonomic richness will be more explained by limnological variables and the functional variation by environmental structural variables. The data comprise a time scale of 14 years. It was sampled eight limnological variables and four habitat structural variables, besides the water level. Fish samples were realized using seining nets. Functional diversity was evaluated from six functional traits, from which functional dispersion and functional redundancy for each sample were calculated, besides the taxonomic richness. Regression models were built utilizing the three indices as response variables and environmental variables as predictors of the community variation. The results showed that the taxonomic richness was influenced by limnological and structural variables. Functional dispersion significantly varied only with structural variables and functional redundancy with two limnological variables. In addition, it was found a high functional redundancy at these sites, varying significantly with concentration of chlorophyll in water in a negative way. This may suggests that oligotrophic environments present more similar species, possibly acting as an environmental filter, which coincides with the current oligotrophication process in the studied environment.